Influence Organizational Commitment , Motivation Work and Compensation on the Performance of Bank Syariah Indonesia Employees in the South Sumatra and Bangka Belitung Region - Herlian Agung Fahmi; Muhammad Idris; Maftuha Nurrahmi (International Journal of Marketing & Human Resource Research, 2026)
This study aims to determine: (1) the effect of organizational commitment, work motivation, and compensation on the performance of marketing employees at Bank Syariah Indonesia in the South Sumatra and Bangka Belitung regions; (2) the effect of organizational commitment on the performance of marketing employees; (3) the effect of work motivation on the performance of marketing employees; and (4) the effect of compensation on the performance of marketing employees at Bank Syariah Indonesia in the South Sumatra and Bangka Belitung regions. This research is an associative study. The variables examined in this study include organizational commitment, work motivation, compensation, and employee performance. The population consists of all marketing employees at Bank Syariah Indonesia in the South Sumatra and Bangka Belitung regions, totaling 101 employees. The sampling technique applied was proportionate stratified random sampling. Primary data were collected using questionnaires. The data were analyzed using multiple linear regression. The results indicate that: (1) organizational commitment, work motivation, and compensation have a significant effect on the performance of marketing employees at Bank Syariah Indonesia in the South Sumatra and Bangka Belitung regions; (2) organizational commitment has a significant effect on employee performance; (3) work motivation has a significant effect on employee performance; and (4) compensation has a significant effect on the performance of marketing employees at Bank Syariah Indonesia in the South Sumatra and Bangka Belitung regions